Assessing the impact of trade liberalization on unemployment, food security and energy poverty in Sub-Saharan Africa : a three-essay approach - (:unkn) unknown (My University, 2025)
This thesis aims to contribute to the existing literature on the links between trade liberalization and socio-economic issues in Sub-Saharan Africa, with a particular focus on the Sustainable Development Goals (SDGs) targets of unemployment, food security and energy poverty. Essay 1 analyses the impact of tradel iberalization on unemployment. We find that trade liberalization contributes to reducing unemployment. In essay 2, we assess the impact of cereal import openness on the prevalence of undernourishment in SSA. We show that cereal imports increase food insecurity in the region. Essay 3 addresses the issue of energy poverty. We show that a reduction in tariff rates is associated with an increase in access to clean fuels, which helps to alleviate energy poverty.
Keywords: African Research